2017
DOI: 10.1002/hup.2609
|View full text |Cite
|
Sign up to set email alerts
|

Updating of working memory in ecstasy polydrug users: Findings from fNIRS

Abstract: Aims/Objectives: Cognitive deficits are now well documented in ecstasy (MDMA) users with type and relative demand of task emerging as important factors. The updating component of executive processes appears to be particularly affected. The study reported here used fNIRS imaging to investigate changes in cortical haemodynamics during memory updating. Method: Twenty Ecstasy users and 20 nonusers completed verbal and spatial memory updating tasks while brain blood oxygenation and deoxygenation change was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In addition to this, four subregions of the PFC were also considered, which were defined as follows: the R-LPFC included Channels 1 to 4, the R-MPFC included Channels 5 to 8, the L-MPFC included Channels 9 to 12, and the L-LPFC included Channels 13 to 16. Several studies using the same or similar devices have examined these PFC subregions as defined earlier (e.g., Anderson et al., 2018; Aranyi, Charles, & Cavazza, 2015; Cavazza, Aranyi, & Charles, 2015; Liang et al., 2016; Montgomery, Fisk, & Roberts, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, four subregions of the PFC were also considered, which were defined as follows: the R-LPFC included Channels 1 to 4, the R-MPFC included Channels 5 to 8, the L-MPFC included Channels 9 to 12, and the L-LPFC included Channels 13 to 16. Several studies using the same or similar devices have examined these PFC subregions as defined earlier (e.g., Anderson et al., 2018; Aranyi, Charles, & Cavazza, 2015; Cavazza, Aranyi, & Charles, 2015; Liang et al., 2016; Montgomery, Fisk, & Roberts, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The NASA Task Load Index (NASA-TLX; Hart & Staveland, 1988) was used, in which participants were asked to self-report their subjective levels of six states on a 20-point scale: mental demand, physical demand, temporal demand, performance, effort, and frustration. This has been used in other studies involving listening effort (e.g., Ahlstrom et al., 2014) as well as in studies using fNIRS to measure cortical oxygenation during an n-back task (e.g., Montgomery et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Significant main effects of Stage at optodes 4, 6 and 8 indicated that oxygenation decreased from baseline over the five stages; given the inverse relationship between O 2 Hb and HHb, it can be assumed that this would indicate an increase in HHb. Increases in HHb are observed where there is an increase in oxygen consumption in a brain region ( Obrig & Villringer, 2003 ), and this increase in oxygenation consumption is indicative of an increase in cognitive demand/monitoring requiring areas of the PFC over the 5 stages (e.g., Funahashi, 2017 ; Montgomery et al, 2017 ; Roberts & Montgomery, 2015 ). In optode 9, the significant main effect of Stage reflects increases in glucose and oxygen utilization in the PFC as the stages progressed.…”
Section: Discussionmentioning
confidence: 99%
“…A final key issue that this study aims to shed further light on is the value of fNIRS assessments in addiction treatment. In the past 2 years, this technique has been used in the assessment of anxiety in heroin users [67], working memory in ecstasy users [68] and investigations of gambling [69] and Internet addiction [70]. While the simplicity, cost-effectiveness and lack of physical restrictiveness noted earlier are all attractive features of the device, it must be recognised that the bulk of the limbic system, which plays a crucial role in substance addiction [71], cannot be imaged using fNIRS.…”
Section: Discussionmentioning
confidence: 99%